Pengaruh Profitabilitas, Risiko Kredit, Dan Efisiensi Operasional Terhadap Nilai Bank Dimoderasi Good Corporate Governance - Prameswari Rasydina Nadia; Mariana Mariana (MEASUREMENT : Jurnal Program Studi Akuntansi, 2026)
This study aims to analyze the effect of profitability, credit risk, and operational efficiency on firm value with Good Corporate Governance (GCG) as a moderating variable in conventional commercial banks listed on the Indonesia Stock Exchange for the period 2020-2024. This study employs a quantitative approach using secondary data in the form of annual financial statements obtained from the official IDX website. The sampling technique used is purposive sampling, resulting in 205 observations from 41 banks over five years of observation. The data analysis methods applied are multiple linear regression and Moderated Regression Analysis (MRA) using SPSS software. The results show that profitability has a significant negative effect on firm value, credit risk has a significant positive effect, and operational efficiency has a significant negative effect on firm value. Meanwhile, GCG is not proven to moderate the effect of the three independent variables on firm value, classifying GCG as a homologizer moderator or potential moderation.